#### Answer

$NM = \frac{1}{3}a+\frac{1}{2}b$

#### Work Step by Step

We can find the length of NM:
$NM = NB + BM$
$NM = (AB-AN)+BM$
$NM = (a - \frac{2}{3}a)+\frac{1}{2}b$
$NM = \frac{1}{3}a+\frac{1}{2}b$

Published by
Brooks Cole

ISBN 10:

ISBN 13:

$NM = \frac{1}{3}a+\frac{1}{2}b$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.